Pembelajaran Belajar Bahasa Arab di Madrasah Ibtidaiyah Melalui Model Pembelajaran Make a Match - Muhammad Taufik (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2021)
This article presents the results of classroom action research on Arabic learning at madrasah ibtidaiyah (Islamic elementary school) level through the make a match learning model. Data were collected using tests, observations, documentation, and reflection in two cycles covering the stages of planning, action, observation, and reflection. The results of the qualitative analysis show that the students’ learning outcomes in the form of the average daily test scores changed after being exposed to the learning model. The achievement of classical completeness also increased from cycle I to cycle II. This study suggests that the make a match learning model can be applied in Arabic learning at the madrasah ibtidaiyah level to help improve the quality of student learning in the classroom.Keywords:Arabic language learning; cooperative learning; make a match